Vi/ver o corpo: velar/desvelar/revelar - Leal, Cristiane Ziegler (2019)
This research is located within the scope of Art and Technology and has as objective the accomplishment of a poetic work in photography and Augmented Reality that brings the body, my body, as object of study. From this object of study I question the diversity and prejudices, the aesthetic bodily models in the technological society, where the image has become the ideal medium of visibility and communication between individuals. Thinking that everything that involves the body is a matter of image, that the photograph questions what it reveals, in the case the body and the problematic that it encloses. The body, our body is built from the look of the other, so it is the subject of countless considerations that work the imaginary. Photography as poetic sustains the questions concerning the body, for it combines exteriority. The materiality of which it reveals induces what lies outside its space of representation. The relationship with the concepts Velar / Unveil / Reveal explains the pertinence that they have in this research, considering that it addresses not only the poetic object's invoice but also what is seen, as a support of the poetic discourse of research. For that, it has as theoretical and conceptual guidelines the studies of authors such as David Le Breton, Lúcia Santaella, Edmond Couchot, Vilém Flusser, Marcel Mauss, André Rouille, among others who are equally important in the foundation of the poetic proposal. As a visual and thematic reference, it approaches, mainly, the poetics of Fernanda Magalhães and Jenny Saville, contributing with the reflections in the contemporary art in relation to the body.